Makna Melahirkan di Rumah bagi Seorang Perempuan - Wiwit Kurniawati; Imami Nur Rachmawati; Yati Afiyanti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2017)
Peristiwa persalinan adalah peristiwa normal dalam kehidupan suatu keluarga, sehingga melahirkan di rumah dengan ditolong tenaga kesehatan merupakan pilihan yang bisa dilakukan oleh perempuan. Studi kualitatif fenomenologi untuk menggali makna melahirkan di rumah bagi perempuan yang melahirkan ditolong oleh tenaga kesehatan belum banyak dilakukan. Studi ini merupakan bagian dari studi yang lebih besar tentang Pengalaman Perempuan selama Proses Persalinan di rumah di tolong tenaga kesehatan. Tujuh partisipan yaitu perempuan yang telah melewati proses persalinan di rumah dengan ditolong oleh tenaga kesehatan di wilayah kerja sebuah puskesmas di Kabupaten Malang berpartisipasi pada penelitian ini. Data dikumpulkan melalui wawancara mendalam sebanyak dua kali yang dilengkapi dengan catatan lapangan. Wawancara direkam kemudian dibuat transkrip wawancara. Hasil penelitian menemukan tiga tema tentang makna melahirkan di rumah yang dirasakan oleh partisipan, meliputi melahirkan sebagai kodrat perempuan, kebahagiaan bagi seorang perempuan yang melahirkan di rumah dan makna pembelajaran bagi keluarga ketika ibu melahirkan dirumah. Hasil penelitian ini memberikan informasi yang bermanfaat dalam penentuan kebijakan untuk membuat desain program maupun intervensi keperawatan guna membantu memenuhi berbagai kebutuhan kesehatan ibu bersalin di rumah. Abstract The Meaning of Home Birth for a Woman. Pregnancy and childbirth are a normal and healthy moments in life of the family. Home birth experience assisted by the health professionals can be a woman’s choice. A study of qualitative phenomenology about the meaning of home birth for women assisted by health provider is still rare. This study is a part of a research about women’s experience during labor with home birth assisted by the health providers. Seven women experienced child birth processes at home with the assisting of health providers in a public health center in Malang municipal, East Java. Data was collected by conducting two interviews along with the field notes. The interview was recorded, than, transcribed. The research finding discussed about the women experiences of home birth processes assisted by the health providers. Furthermore, this research discussed about the deep meaning of home birth for a women, including the nature of birthing and childbirth as women, the happiness for a woman who experienced child birth processes at home and the meaning the family life learning when the mother experiencing child birth processes at home. The result of this research is considered for giving information in determine policy in designing program of nursing intervention design for assisting and providing the women health needs in home birth processes. Keywords: meaning, home birth, women, health provider